Increased power generation from a new sandwich-type microbial fuel cell (ST-MFC) with a membrane-aerated cathode - Taskan, Banu (Pergamon-Elsevier Science Ltd, 2020)
In this study, a new aeration approach was used for cathode by offering an efficient and cost-effective alternative for practical applications of microbial fuel cells. Therefore, a new sandwich type microbial fuel cell was constructed having three chambers (two anodes and one cathode) was constructed. This sandwich type microbial fuel cell was fed with a mixture of sewage sludge and algae biomass (at the ratio of 1:1). The pure oxygen gas was delivered to the cathode by using hydrophobic hollow fiber gas transfer membranes at different gas pressures (2, 4, 6, 8 and 10 psi). The results revealed that this new sandwich type microbial fuel cell achieved a good performance, and the max power density increased from 1448 mW m(-2) to 26680 mW m(-2) with an increase in oxygen pressure from 2 psi to 10 psi. The presence of electrochemically active bacteria-colonization on the anode's surfaces was revealed by microscopic observations and molecular analysis. This study demonstrated the feasibility of using a hollow fiber gas transfer membrane and a mixture of sewage sludge and algae biomass to enhance power production by sandwich type microbial fuel cell.
Keywords: Sandwich-type MFC; Gas-transfer membrane; Pure oxygen; Sewage sludge; Algae biomass